New combinatorial versions of Göllnitz-Gordon identities - Agarwal A.K.; Rana M. (Utilitas Mathematica, 2009)
In this paper we establish an infinite family of 3-way combinatorial identities using n-color partitions and lattice paths. We discuss some particular cases which provide several new combinatorial versions of the Göllnitz-Gordon identities.